KARAKTERISTIK MUTU NUGGET UDANG KERING DENGAN NANGKA MUDA - Idwal Suripto; Evy Rossi; Yelmira Zalfiatri (Fakultas Pertanian Universitas Riau, 2022)
The purpose of this study was to obtain a comparison of dried shrimp nuggets and young jackfruit to quality (moisture content, ash content, protein content, fat content, and crude fiber content) and sensory nugget of shrimp and young jackfruit. The research method used a completely randomized design with four treatments and four replications. The treatments consisted of UN1 dried shrimp: young jackfruit (70:30), UN2 dried shrimp:young jackfruit (60:40), UN3 dried shrimp:young jackfruit (50:50), and UN4 dried shrimp: young jackfruit (40:60). The data obtained were analyzed statistically using the analysis of variance and continued with the Duncan’s Multiple range test (DMRT) at the 5% level. The results of the analysis showed that the combination of dried shrimp and young jackfruit had a significant effect on moisture, ash, fat, protein and crude fiber content, as well as descriptive and hedonic sensory assessments such as color, aroma, taste and texture. The best treatment was UN1 dried shrimp: young jackfruit (70:30) with the moisture content was 58.68%, ash content was 4.44%, fat content was 4.14%, protein content was 11.65%, and crude fiber content was 0.99%. Descriptive sensory assessment was brown in color, very flavorful of dried shrimp, very dried shrimp taste, and chewy texture and hedonic judgments are favored by the panelists.